A Virtual Ethnography Study: The Role of Cultural Radios in Campursari Music Proliferation in East Java - Zainal Abidin Achmad; Rachmah Ida; Mustain Mustain (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
Campursari music is a trend on the radio and a favorite of the people of East Java, so it is shifting towards popular culture. This study aims to uncover the proliferation of campursari music and the role of cultural radios. This qualitative research uses a virtual ethnography method, which focuses on the physical presence and virtual text together. The subjects are technology (radio and communication technology on the internet), humans (radio listeners), physical interactions, and virtual interactions. Data collection used participant observation through observation and interviews offline and online in the form of various texts, writings, images, and audiovisuals on Facebook, Twitter, WhatsApp, Instagram, and Youtube. The informants of this study were four cultural experts, namely: Sumadi, Anton Sani, Ibnu Hajar, and Juwono. This study carried out participatory involvement for one year in the virtual world and 30 days living in four cities: Surabaya, Nganjuk, Banyuwangi, and Sumenep. Manthous's campursari music is a fusion of pentatonic and diatonic scales despite the addition of various musical instruments. It has several sub-genres, including campursari janger, campursari kendang-kempul, campursari keroncong dangdut, campursari dangdut Madura, campursari jaranan dangdut, campursari dangdut koplo, campursari dangdut hip-hop, and campursari dangdut acoustic. Cultural programs and campursari music reinforce the reliability of radio to maintain local culture (Javanese, Madura, Using). They are a means of maintaining local identities to stem global culture. No matter how hard the invasion of foreign culture, can not disrupt the local tastes of people. Campursari music proliferation is a modification to traditional music to serve the tastes of the people, to avoid it from extinction. Campursari music must be able to adapt to the current era. The four radio cultures in East Java make campursari music a primary commodity to attract radio listeners and as part of the lives of local people.